Detection of Outlier Observations in Piezometric Measurements: A Case Study in the Southern Region of Poland - Lach, Stanisław (Geomatics and Environmental Engineering, 2021)
One of the main modes of monitoring the geotechnical conditions of earth dams is piezometric measurement, which measures water levels in an open piezometer or water pressure in a closed piezometer. During piezometric measurements, various types of factors can cause disturbances in these measurements that take the form of systematic, accidental, or obvious mistakes. Before measurements from open or closed piezometers are analyzed, outliers due to coarse errors should be detected and rejected. Such observations may significantly influence the result of the analysis and cause erroneous assessment and interpretation of the phenomenon studied. To do this, statistical tests must be applied so that the doubtful measurement can be accepted or rejected at the assumed significance level. This paper uses five statistical tests for identifying and rejecting outliers: the Q-Dixon test, the Grubbs test, as well as the Hampel test, the Iglewicz and Hoaglin test, and the Rosner test. The aim of this article is to try to identify the most suitable test for periodic piezometric measurements. The scope of the study includes the analysis of piezometric measurements for the Czaniec Dam for the multi-year period 2017‑2020.